Dispersion of ventricular repolarisation: a marker of ventricular arrhythmias in patients with previous myocardial infarction. Issue 4 (1st October 1997) - Zaidi, M; Robert, A; Fesler, R; Derwael, C; Brohet, C
Abstract : Objective: To examine whether, in coronary patients after myocardial infarction, the dispersion of ventricular repolarisation measured through QT and JT intervals from a surface electrocardiogram could allow separation of those with ventricular tachyarrhythmias (VT) complicating their myocardial infarct from those without. Design: A retrospective comparative study. Setting: University hospital. Patients: 39 patients with myocardial infarction complicated by VT, 300 patients after myocardial infarction without arrhythmic events, and 1000 normal subjects. The myocardial infarction groups were divided into anterior, inferior, and mixed locations. Interventions: A computer algorithm examined an averaged cycle from a 10 second record of 15 simultaneous leads (12 lead ECG + Frank XYZ leads). After interactive editing, four intervals were computed: QTapex, JTapex, QTend, and JTend. For each interval, the dispersion was defined as the difference between the maximum and minimum values across the 15 leads. Results: The mean values of all four dispersion indices were higher in patients with myocardial infarction than in normal subjects (p < 0.01). In the infarct groups, patients with VT had significantly greater mean and centile dispersion values than those without VT. For instance, the 97.5th centile value of QTend was 65 ms in normal individuals, 90 ms in infarct patients without arrhythmia, and 128 ms in those with VT; 70% of the infarct patients who developed serious ventricular arrhythmias had values exceeding the 97.5th centile of the normal group, while only 18% of the infarct patients without arrhythmia had dispersion values above this normal upper limit. Among the infarct patients, nearly half of those (18 of 39) with tachyarrhythmias had dispersion values that exceeded the 97.5th centile of those without arrhythmia. Conclusions: Dispersion of ventricular repolarisation may be a good non-invasive tool for discriminating coronary patients susceptible to VT from those who are at low risk.